Da modelagem matemática à modelação: um estudo sobre a propagação da podridão em maçãs - Gomes, Wellington Luiz Fraga (2019)
This paper proposes a study of the theoretical and methodological aspects of modelling and modelling mathematical as a means of improvement in teaching, but uses the stages of modelling, but it is not modelling, because it allows to reconcile the school schedule with the curriculum that are guided and are in accordance with the official documents: National Curriculum Parameters (PCN) and Common National Curriculum Base (BNCC). The elaboration of this work was carried out with as main theoretical references: Bassanezi, Meyer, Caldeira, Malheiros and Biembengut, which despite somewhat distinct views on modelling, agree with the idea that students when submitted to a Real problem situation is more interesting and reflective to learn. We confront the objectives of modelling and modelling mathematical, besides emphasizing their relevance both in the Brazilian and international scenario. For the application of modelling mathematical we are based on the real problem situation of the propagation of rot in apples according to Bassanezi's work, where several mathematical topics were explored, such as flat geometry, spatial geometry and sequences. The proposal for the application of the modelling mathematical process was through Online Directed Studies (ED), extra class, and after classes sharing doubts and solutions of these ED, in addition to the participation of the teacher as mediator, sharpening the discussions and clarifying some doubts, and encouraging each educating to conjecture according to their look at the problem situation. The teacher as a mediator did not arrive in the room with ready-made solutions, nor stating which answers were right or wrong, but leading them to think about validating their own ideas (model). The application of Maematic Modelling mathematical is not considered in this work as the panacea of education, but as a proposal for improvement in teaching, and can be applied without restrictions both in elementary and high school. When analyzing the application of the work proposal through ED, we inferred that there was significant relevance for students in the teaching-learning process, because it aroused in them the interest and seeking knowledge when they perceived mathematics as tool to solve the problem, in addition to the freedom that the electronic environment enabled them to expose their ideas without fear of being right or wrong. We also propose the application of other work proposals and the realization of an experiment that can help in the systematization of the issues addressed.